Clinical features associated with ADB-BUTINACA exposure in patients attending emergency departments in England. (3rd October 2022) - King, A.; Hill, S. L.; Pucci, M.; Bailey, G.; Keating, L.; Macfarlane, R.; Cantle, F.; Hudson, S.; Thomas, S. H. L.
Abstract: Objective: Synthetic cannabinoid receptor agonists (SCRA) are commonly encountered new psychoactive substances. Here we report the recent detection of ADB-BUTINACA in samples from patients attending United Kingdom emergency departments with toxicity after suspected drug misuse and describe the associated clinical features. Methods: Consenting adults (≥16 y) presenting to participating hospitals with toxicity after suspected drug misuse have been included in the Identification Of Novel psychoActive substances (IONA) study since March 2015. Demographic and clinical features are recorded and blood and/or urine samples analysed using high-resolution accurate mass liquid chromatography-mass spectrometry. Results: By December 2021, analytical data were available for 1279 IONA participants and ADB-BUTINACA was detected in at least one sample from 10 (9 males, age range 16–51 median 45 years), all presenting since February 2021. Smoking 'spice' was reported by four patients, two had ingested edible "cannabis" gums and four reported heroin use (2 intravenous, 1 smoked, 1 route not known). Co-use of pregabalin (oral) and crack cocaine (smoked) were also reported. In 3 cases ADB-BUTINACA was the only substance detected, while in seven other substances of misuse were also detected including other SCRA, opioids, benzodiazepines cocaine and pregabalin. Clinical features reported in these 2 groups respectively included reduced level of consciousness (3/3, 6/7), agitation (0/3, 4/7), tachycardia (0/3, 3/7), seizures (1/3, 1/7), hallucinations (1/3, 1/7), hypotension (1/3, 1/7). Metabolic acidosis (1/3, 0/7) and respiratory acidosis (1/3, 0/7), All 10 patients recovered with supportive care, including intubation and ventilation for one case. The median length of hospital stay was 19 h (range 2.6–131 h). Conclusions: ADB-BUTINACA has recently emerged as a drug of misuse in England. Clinical features of toxicity are consistent with those of other SCRA and include reduced level of consciousness, respiratory and/or metabolic acidosis, seizures, confusion and hallucinations.